Gallium–Carbenicillin Framework Coated Defect‐Rich Hollow TiO2 as a Photocatalyzed Oxidative Stress Amplifier against Complex Infections. (6th September 2020) - Yang, Jingjing; Wang, Chao; Liu, Xinli; Yin, Yi; Ma, Yong‐Hao; Gao, Yanfeng; Wang, Yuzhen; Lu, Zhenda; Song, Yujun
Abstract: Development of new strategies with high antimicrobial capability against complex bacterial infections is still challenging. Herein, a three‐in‐one synergistic antimicrobial platform is presented based on gallium–carbenicillin framework coated defect‐rich hollow TiO2 nanoshells (H‐TiO2− x @MOF), for simultaneous eradicating methicillin‐resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa (PA) in complex infections, which are the two most common bacteria in wounds. The metal gallium can disrupt bacterial antioxidation system using a "Trojan horse" strategy by substituting iron in the antioxidant enzymes, and finally increase bacterial susceptibility to oxidants. Meanwhile, oxygen‐deficient hollow TiO2− x nanoshells (H‐TiO2− x NSs) can efficiently bind to the bacteria and promote local generation of abundant reactive oxygen species (ROS) under visible‐light irradiation. Thus, the combination of gallium (antioxidant enzyme inhibitor) and black H‐TiO2− x NSs (ROS generator) constitutes a photocatalyzed oxidative stress amplifier that can boost ROS accumulation to destroy pathogens thoroughly. In addition, carbenicillin (Car), as the organic ligand coordinated to gallium ion, also acts as a broad‐spectrum antibacterial agent against PA and shares the responsibility for combating complex infections simultaneously. In view of the superior antibacterial ability, accelerated healing of infected wounds, and good biosafety, the H‐TiO2− x @MOF potentially provides an alternative antibacterial agent to combat complex bacterial infections. Abstract : H‐TiO2− x @MOF nanohybrids that combine traditional antibiotics and a photocatalyzed oxidative stress amplifier can be readily used in the defense against complex infections. H‐TiO2− x @MOF is degraded in the wound site. Then, the photocatalyzed oxidative stress amplifier, consisting of H‐TiO2− x and gallium, together with carbenicillin exhibits a synergistic effect on the eradication of complex infection caused by Pseudomonas aeruginosa and methicillin‐resistant Staphylococcus aureus .